THE IMPORTANCE OF ENGLISH LANGUAGE IN RAILWAY LOGISTICS EDUCATION: THE CASE OF KOKAND RAILWAY TECHNICAL COLLEGE - Asatillayeva Sehriyo Karimjon qizi (TADQIQOTLAR, 2026)
Annotation: In the context of globalization, logistics and railway transport require specialists who are able to communicate effectively at the international level. English has become the main language of professional interaction in logistics, transport documentation, and international cooperation. This article examines the importance of English language teaching in railway logistics education with special reference to Kokand Railway Technical College. The study focuses on the role of English lessons, teaching styles, learning environment, and professional orientation of language instruction. Particular attention is paid to the integration of English for Specific Purposes (ESP) into the curriculum and the future development of students’ English competence. The findings indicate that professionally oriented English instruction significantly enhances students’ readiness for work in the international logistics sector.